Implementation of Punishment for Perpetrators of Aggravated Theft Based on the New Criminal Code: Implementasi Pemidanaan Terhadap Pelaku Tindak Pidana Pencurian Dengan Pemberatan Berdasarkan KUHP Baru - Reano, Arfan; Prasetyo, Boedi (Indonesian Journal of Law and Economics Review, 2025)
General background: Aggravated theft remains one of the most prevalent property crimes in Indonesia, generating significant social and economic harm. Specific background: The enactment of the New Criminal Code (Law No. 1 of 2023) introduces substantial reforms to the formulation and classification of aggravated theft, replacing the long-standing provisions under Article 363 of the former Criminal Code. Knowledge gap: Despite these changes, there is limited scholarly analysis regarding how the new provisions affect sentencing practices, evidentiary assessment, and legal certainty within the criminal justice system. Aims: This study analyzes the implementation of criminal sentencing for aggravated theft under Article 477 of the New Criminal Code and compares it with the regulatory framework of the previous code. Results: The findings indicate that the New Criminal Code provides clearer, more systematic, and more coherent formulations of aggravating factors, alongside more proportional sentencing scales, thereby facilitating investigation, prosecution, and judicial decision-making. Novelty: This study demonstrates that the restructuring of aggravated theft provisions enhances interpretive consistency and reduces ambiguity in legal application. Implications: Overall, the revised provisions strengthen sentencing effectiveness, reinforce deterrence, and establish greater legal certainty in adjudicating aggravated theft cases. Highlights: Clarifies the shift from Article 363 (Old KUHP) to Article 477 (New KUHP) in defining aggravated theft. Highlights improved clarity, structure, and proportionality in the New Criminal Code’s sentencing framework. Emphasizes the enhanced legal certainty and consistency for law enforcement and judicial practice. Keywords: Aggravated Theft, New Criminal Code, Sentencing, Legal Certainty, Proportionality